Republican Baths at Pompeii: New Research on the Development and Function - Trümper, Monika; Esposito, Domenico; Brünenberg, Clemens; Ferrandes, Antonio F.; Pardini, Giacomo; Pegurri, Alessandra; Robinson, Mark (Archäologischer Anzeiger, 2025)
The Republican Baths in Pompeii were excavated and briefly published in 1950 by Amedeo Maiuri. While one of the few known Late Republican baths, the complex has received little attention since 1950. Therefore, a research project initiated in 2015 by the Freie Universität Berlin and Oxford University aimed to investigate the construction date, development, function, urban context, and socio-cultural significance of the Republican Baths at Pompeii. This article presents the main results of fieldwork carried out between 2015 and 2019 that entailed a systematic reassessment of the architecture and decoration and stratigraphic excavations in 24 areas. After general remarks on the architecture and decoration, the 21 rooms of the baths are assessed one after another, discussing the architecture, decoration, function, and possible changes. The concluding evaluation argues that a private investor built the baths after 130/120 BC with separate sections for men and women; the baths were once remodeled, presumably after Pompeii became a Roman colony in 80 BC, before being abandoned and overbuilt around 30/20 BC.